Berberine alleviates ischemia reperfusion injury induced AKI by regulation of intestinal microbiota and reducing intestinal inflammation - Aijing Huo; Fengmei Wang (BMC, 2024)
Abstract Background It has been found that a variety of host disease states can exacerbate intestinal inflammation, leading to disruption of intestinal barrier function. Changes in the composition of the intestine microbiota, which affect downstream metabolites in turn, ultimately react against the host. Objectives We revealed the mechanism of berberine as an intestinal protective agent in rats with renal ischemia-reperfusion injury acute kidney injury (AKI). Methods HE staining was performed to evaluate the pathological changes in the colon and kidney. 16 S rRNA analysis was performed to assess the intestinal microbiota. Intestine TLR4/NF-κB expression was assessed by western blot. Q-RT-PCR was performed to detect TLR4 in intestine and IL-6 and KIM-1 gene expression in the kidney. SPSS 22.0 was used to compare the data. Results Rats with AKI exhibited increased relative abundances of Proteobacteria and Bacteroidetes and decreased relative abundances of Lactobacillus, Ruminococcus and Lachnospiraceae belonging to the phylum Firmicutes. The Sirt1-NF-κB-TLR4 pathway was involved in the occurrence process, accompanied by intestinal inflammation and oxidation. Berberine reversed the appeal change. Conclusion Berberine inhibits the intestinal biological barrier of Proteobacteria, reduces LPS production, exerts an anti-inflammatory effect, and delays the progression of AKI.